Theology and the mirror of Scripture : a mere evangelical account - Vanhoozer, Kevin J.; Treier, Daniel J., 1972- (Downers Grove, Illinois, IVP Academic, 2015)
Evangelicalism has long been a hotly disputed label, and what counts as evangelical theology is often anyone's guess. Is evangelicalism a static bounded set defined by clear doctrinal limits, or is it a dynamic centered set without a discernible circumference? In this inaugural volume in the Studies in Christian Doctrine and Scripture, Kevin Vanhoozer and Daniel Treier present evangelical theology as an "anchored" set, rooted in the Trinity. In response to increasing evangelical fragmentation, Theology and the Mirror of Scripture offers a clarion call to reconceive evangelical theology theologically by reflecting on the God of the gospel as mirrored in Scripture. Such "mere" evangelical theology will be an exercise in Christian wisdom for the purpose of building up the fellowship of saints. Read more: http://www.ivpress.com/cgi-ivpress/book.pl/code=4076#ixzz3oSYE7Bpl --Publisher
In my father's house, many evangelical rooms -- The agenda: the material and formal principles of evangelical theology -- The gospel of God and the God of the gospel: the reality behind the mirror -- From canonical cradle to doctrinal development: the authority of the mirror -- The analysis: the practice of evangelical theology -- In search of wisdom -- In need of theological exegesis -- In fellowship with the saints -- In pursuit of scholarly excellence -- A city of light: the reality in front of the mirror.
Includes bibliographical references [pages 263 - 287] and indexes.
Keywords: Bible -- Evidences, authority, etc; Bible -- Criticism, interpretation, etc; Reformed Church -- Doctrines; Evangelicalism; Word of God (Christian theology); Criticism, interpretation, etc